Liquid PRF Reduces the Inflammatory Response and Osteoclastogenesis in Murine Macrophages - Kargarpour, Zahra; Nasirzade, Jila; Panahipour, Layla; Miron, Richard J.; Gruber, Reinhard (Frontiers in Immunology, 2021)
Macrophage activation and osteoclastogenesis are hallmarks of inflammatory osteolysis and may be targeted by the local application of liquid platelet-rich fibrin (PRF). Liquid PRF is produced by a hard spin of blood in the absence of clot activators and anticoagulants, thereby generating an upper platelet-poor plasma (PPP) layer, a cell-rich buffy coat layer (BC; termed concentrated-PRF or C-PRF), and the remaining red clot (RC) layer. Heating PPP has been shown to generate an albumin gel (Alb-gel) that when mixed back with C-PRF generates Alb-PRF having extended working properties when implanted in vivo. Evidence has demonstrated that traditional solid PRF holds a potent anti-inflammatory capacity and reduces osteoclastogenesis. Whether liquid PRF is capable of also suppressing an inflammatory response and the formation of osteoclasts remains open. In the present study, RAW 264.7 and primary macrophages were exposed to lipopolysaccharides (LPS), lactoferrin, and agonists of Toll-like receptors (TLR3 and TLR7) in the presence or absence of lysates prepared by freeze-thawing of liquid PPP, BC, Alb-gel, and RC. For osteoclastogenesis, primary macrophages were exposed to receptor activator of nuclear factor kappa B ligand (RANKL), macrophage colony-stimulating factor (M-CSF), and human transforming growth factor-β1 (TGF-β1) in the presence or absence of PPP, BC, Alb-gel, RC lysates and hemoglobin. We show here that it is mainly the lysates prepared from PPP and BC that consistently reduced the agonist-induced expression of interleukin 6 (IL6) and cyclooxygenase-2 (COX2) in macrophages, as determined by RT-PCR and immunoassay. With respect to osteoclastogenesis, lysates from PPP and BC but also from RC, similar to hemoglobin, reduced the expression of osteoclast marker genes tartrate-resistant acid phosphatase (TRAP) and cathepsin K, as well as TRAP histochemical staining. These findings suggest that liquid PRF holds a potent in vitro heat-sensitive anti-inflammatory activity in macrophages that goes along with an inhibition of osteoclastogenesis.